ECONOMIC SECURITY OF AGRICULTURAL ENTERPRISES OF CHERNIHIV REGION, WAYS AND PROSPECTS OF DEVELOPMENT - STADNYK, VICTORIYA; DVORNYK, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The concepts and essences of economic security are presented, the general characteristics, analysis and assessment of the natural resource and socio-economic potential of the Chernihiv region are presented, the proportions, structure and pace of development of its economic complex are investigated, as well as an analysis of the organization and development of the social sphere and foreign economic activity of the region is made. The purpose of the work is to develop theoretical and methodological principles and scientific and practical approaches to the problem of economic security of Chernihiv region. In accordance with the goal, the author of the article sets the following tasks: to reveal the concept and determine the essence of economic security of management in the Chernihiv region.